Pendampingan Pengajuan Perizinan Pengurusan Sertifikasi Halal Sebagai Legalitas Produk UMKM Emiro - Viga Esa Rizkhie; Eka Farida (I-Com: Indonesian Community Journal, 2024)
ABSTRACT Product assistance program for micro, small and medium enterprises (MSMEs). Management Halal Certificate through “SEHATI” program carried out through outreach activities and programs assistance in processing halal certification as an effort to increase consumer confidence in market share, because the products being marketed are legal smart and competent. Apart from that, with the government's "SEHATI" program in the halal certification program free of charge, it is hoped that this can provide benefits and added value for MSMEs in register product halal management. Research methods to do is to use it method Qualitative descriptive research is used in this type of research arena . This service uses socialization methods and mentoring directly to MSME actors processing completeness of valid/legal certificate permits . Keywords : Mentoring ; MSMEs, Certification